Frequency of In-Stent Restenosis among Different 2nd/3rd Drug Eluting Stents in Patients Presenting with ACS/Angina at Trtiary Cradiac Care Centre - Shakir Ghaffar; Waheed-Ur- Rehman; Alam Khan; Muhammad Amad Abbasi; Sajjad Ali; Muhammad Naeem Tariq; Zeeshan Arif; Syed Khurram Shahzad; Javeria Kamran (Pakistan Armed Forces Medical Journal, 2022)
Objective: Primary objective was to determine the frequency of in-stent restenosis (ISR) among second/third generation drug eluting stents (DES), diagnosed angiographically in cardiac catheterization laboratory either in emergency settings or elective stage procedure and to determine the risk factors precipitating ISR.